Assessing financial literacy the case of the officers of Davao Dairy Cooperatives - Canceran, Dexie C.; Acuña, Thaddeus R. (2017)
Financial literacy is identified as a core skill that makes individuals move in a financial environment. Globally, one out of three adults is financially literate and in the Philippines on 25% of the adults can be categorized as such. The operation of cooperative are not exempted from the adverse effects of the low level of financial literacy among individuals, particularly that of the officers who are responsible for the overall direction was challenged by the lack of financial knowledge and application in the form of record keeping and optimizing limited financial capital. In Davao city, the number of member-cooperatives of the Federation of Davao city Dairy Farmer?s Cooperative (FEDDAFC), a major player in the daily supply of milk was reduced due to unsustainable operations. Hence, this study focused in looking into the financial literacy of the officers of the member of the cooperatives of FEDDAFC.
Thesis (BS Agribusiness Economics) -- University of the Philippines Mindanao, May 2017
Confidential